Playing Pattern Analysis of Men’s Single Badminton Matches - Fadhil Abdullah, Mohd; Janep, Mandra; Shahrul Azzfar, Mohamad; Abd Karim, Zulakbal; Rahmat, Azali; Md Nadzalan, Ali (International Journal of Engineering and Technology, 2018)
The objective of this study is to determine the playing pattern of selected men’s single badminton matches during BWF World Championships 2017. Players’ return methods; smash, drop, drive, lob, clear and net performed in the match were notated using notational analysis. The return methods were also analysed based on the place of target; fore left, fore right, mid left, mid right, rear left and rear right. The non-effective returns were also notated. The findings of the playing patterns performed by players are important as this can be used as a source of reference for the players to plan on technical and tactical part during the real match especially in important tournament.